2019
DOI: 10.3233/ch-199001
|View full text |Cite
|
Sign up to set email alerts
|

Shear-dependency of the predicted ideal hematocrit

Abstract: The ideal hematocrit is the hematocrit (Hct) value resulting in the highest value of Hct/viscosity (h/η) ratio and can thus be predicted from viscometric measurements with the use of equations such as Quemada's one which yield the determination of the bell-shaped curve of h/η as a function of Hct. In a series of recent papers we applied this approach to various populations, using viscometry at high shear rate (1000 s -1 ). However the shape of this curve has been reported to be dependent on the shear rate, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…13 Notably, two Asian studies have reported that blood viscosity at admission is higher in patients with stroke secondary to smallartery occlusion than in those with stroke associated with cardioembolism and largeartery atherosclerosis. 14,15 Hematocrit, the mechanical properties of erythrocytes, and plasma viscosity are the primary determinants of whole blood viscosity; 16,17 of these, hematocrit plays a key role. 18 Many previous studies have reported that hematocrit elevation increases stroke risk after adjusting for several variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Notably, two Asian studies have reported that blood viscosity at admission is higher in patients with stroke secondary to smallartery occlusion than in those with stroke associated with cardioembolism and largeartery atherosclerosis. 14,15 Hematocrit, the mechanical properties of erythrocytes, and plasma viscosity are the primary determinants of whole blood viscosity; 16,17 of these, hematocrit plays a key role. 18 Many previous studies have reported that hematocrit elevation increases stroke risk after adjusting for several variables.…”
Section: Discussionmentioning
confidence: 99%
“…Hematocrit, the mechanical properties of erythrocytes, and plasma viscosity are the primary determinants of whole blood viscosity; 16 , 17 of these, hematocrit plays a key role. 18 Many previous studies have reported that hematocrit elevation increases stroke risk after adjusting for several variables.…”
Section: Discussionmentioning
confidence: 99%